TINGKAT PLAGIARISME MAHASISWA PGSD MELALUI PORTOFOLIO BERBASIS TRELLO - St. Muriati, St. Muriati; Dipalaya, Tismi (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Plagiarism is an act of deliberately or unintentionally obtaining credit or value for a scientific work, by quoting part or all of the scientific work of another person, without stating the source accurately and adequately. The purpose of this study was to determine the level of plagiarism of PGSD students through the application of trello-based portfolio learning at Bosowa University, and to change the plagiarism attitude of PGSD students through the application of trello-based portfolio learning. This research is a type of case study research. The population in this study were students of the 2017 PGSD class at Bosowa University. While the sample of this research was conducted by using purposive sampling method, which is based on the characteristics possessed by the selected subjects according to the purpose of the research to be carried out. Combined research methods are an approach to research that combines or links between quantitative and qualitative research methods. Through the research, it was obtained data that the level of similarity index or the level of similarity of trello-based portfolio results to PGSD students at Bosowa University was included in the high category indication. However, the turnitin test is not a determinant of plagiarism but only functions as a tool to make it easier for us to find out indications of plagiarism in an article. In addition, the results show that of the five internal factors of plagiarism, there are three factors that experience changes. This shows a positive attitude towards plagiarism.